2018
DOI: 10.23937/2572-3243.1510049
|View full text |Cite
|
Sign up to set email alerts
|

Oral Ibuprofen Interferes with Cellular Healing Responses in a Murine Model of Achilles Tendinopathy

Abstract: Background: The attempted healing of tendon after acute injury (overloading, partial tear or complete rupture) proceeds via the normal wound healing cascade involving hemostasis, inflammation, matrix synthesis and matrix remodeling. Depending on the degree of trauma and the nature of the post-injury milieu, a variable degree of healing and recovery of function occurs. Post-injury analgesia is often achieved with NSAIDs such as Ibuprofen, however there is increasing evidence that NSAID usage may interfere with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…with IL-1β, has been shown to increase tenocyte migration and proliferation, the capacity for which decreases with age. 80,83,87,88,[100][101][102][103][104][105][106] In this study, we observed a decrease in tenocyte migration and proliferation following inflammatory stimulation in all species (statistically significant for sheep tenocyte proliferation as well as rat and mouse tendon cell migration under constant inflammation) except rats (non-significant trend toward increased proliferation), which may be due to our use of tenocytes from individuals in diseaserelevant age groups. The overall gene expression of human tenocytes was most similar to murine under healthy, equine under transient and ovine under constant inflammatory conditions.…”
Section: Discussionmentioning
confidence: 61%
“…with IL-1β, has been shown to increase tenocyte migration and proliferation, the capacity for which decreases with age. 80,83,87,88,[100][101][102][103][104][105][106] In this study, we observed a decrease in tenocyte migration and proliferation following inflammatory stimulation in all species (statistically significant for sheep tenocyte proliferation as well as rat and mouse tendon cell migration under constant inflammation) except rats (non-significant trend toward increased proliferation), which may be due to our use of tenocytes from individuals in diseaserelevant age groups. The overall gene expression of human tenocytes was most similar to murine under healthy, equine under transient and ovine under constant inflammatory conditions.…”
Section: Discussionmentioning
confidence: 61%
“…In a murine model of Achilles tendinopathy, administration of ibuprofen during the inflammatory stage of healing interfered with extracellular matrix remodeling and ultimately led to decreased tensile strength in the healed tendon. 105 Similar results, including abnormal fiber organization and decreased tensile strength, were seen in a rat model of tendinopathy where ibuprofen was delivered in the first week after injury. However, when delivered after 1 week following injury, no detrimental effects were seen, suggesting that NSAIDs interfere in tendon healing in a time dependent manner, most pronounced in the early, inflammatory phase of healing.…”
Section: Nsaid Usementioning
confidence: 53%
“…For example, NSAIDs treatment suppressed extracellular matrix remodeling and cellular responses in a tendinopathy animal model. 3,9 NSAIDs led to decreased 7,9 or no effect 13,42 on tendon mechanical properties after repair. Rather than completely suppressing the inflammatory response, small-molecule inhibitors can be used to selectively block a specific part of a pathway (eg, the inflammatory arm of NF-κB) to maintain the positive inflammatory response necessary for initiating tendon healing while suppressing the detrimental effects of sustained inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…16 However, broadly suppressing inflammation through nonsteroidal anti-inflammatory drugs (NSAIDs), commonly used postoperatively, is also detrimental to healing. 3,9,13 Therefore, a carefully balanced inflammatory response is necessary for optimal healing (eg, by modulating inflammation at the earliest stages after repair 20 ).…”
mentioning
confidence: 99%